High‐Resolution Magnetic Resonance Imaging of Scalp Arteries for the Diagnosis of Giant Cell Arteritis: Results of a Prospective Cohort Study. Issue 1 (28th December 2016) - Rhéaume, Maxime; Rebello, Ryan; Pagnoux, Christian; Carette, Simon; Clements‐Baker, Marie; Cohen‐Hallaleh, Violette; Doucette‐Preville, David; Stanley Jackson, B.; Salama Sargious Salama, Samih; Ioannidis, George; Khalidi, Nader A.
Abstract : Objective: To examine the concordance between high‐resolution magnetic resonance imaging (MRI) of the scalp arteries and temporal artery biopsy for the diagnosis of giant cell arteritis (GCA). Methods: We conducted a prospective cohort study of patients with suspected GCA. Participants underwent high‐field 3T MRI of the scalp arteries followed by temporal artery biopsy. Arterial wall thickness and enhancement on multiplanar postcontrast T1‐weighted spin‐echo images were graded according to a published severity scale (range 0–3). MRI findings were compared with temporal artery biopsy results and the American College of Rheumatology (ACR) criteria for GCA. Results: One hundred seventy‐one patients were included in the study. Temporal artery biopsy findings were positive in 31 patients (18.1%), and MRI findings were abnormal in 60 patients (35.1%). ACR criteria were met in 137 patients (80.1%). With temporal artery biopsy as the reference test, MRI had a sensitivity of 93.6% (95% confidence interval [95% CI] 78.6–99.2) and a specificity of 77.9% (95% CI 70.1–84.4). The corresponding negative predictive value of MRI was 98.2% (95% CI 93.6–99.8) and positive predictive value was 48.3% (95% CI 35.2–61.6). Conclusion: In patients with suspected GCA, normal findings on scalp artery MRI are very strongly associated with negative temporal artery biopsy findings. This suggests that MRI could be used as the initial diagnostic procedure in GCA, with temporal artery biopsy being reserved for patients with abnormal MRI findings.